Homophilic synaptic target recognition mediated by immunoglobulin-like cell adhesion molecule Fasciclin III. - Kose, H.; Rose, D.; Zhu, X.; Chiba, A. (Development, 1997)
We demonstrate that the cell adhesion molecule Fasciclin III (FAS3) mediates synaptic target recognition through homophilic interaction. FAS3 is expressed by the RP3 motoneuron and its target muscles during synaptic target recognition. The RP3 growth cone can form synapses on muscles that ectopically express FAS3. This mistargeting is dependent on FAS3 expression in the motoneurons. In addition, when the FAS3-negative aCC and SNa motoneuron growth cones ectopically express FAS3, they gain the ability to recognize FAS3-expressing muscles as alternative targets. We propose that homophilic synaptic target recognition serves as a basic mechanism of neural network formation.